Edukasi Vaksinasi Covid-19 di Desa Henda Kabupaten Pulang Pisau Kalimantan Tengah - Herlina Eka Shinta; Angeline Novia Toemon; Ratna Widayati (CV. Multi Kreasi Media, 2022)
Covid-19 is a highly contagious infectious disease. Transmission can be through coughing or sneezing droplets, or indirectly through objects contaminated with droplets from coughs or sneezes of Covid-19 sufferers. One of the reasons is is the lack of public understanding of the importance of the Covid-19 vaccination. One attempt to increase people's understanding is by providing health education about the importance of vaccination as an effort to reduce the incidence of Covid-19. By providing this health education, the public will have good understanding about the importance of Covid-19 vaccination, and will voluntarily participate in the Covid-19 vaccination program to support the government, especially Central Kalimantan Province in suppressing the growth rate of Covid-19 incidence. The purpose of this activity is to increase public awareness. about the importance of the Covid-19 vaccination. This activity was carried out in Henda Village, Jabiren District, Pulang Pisau Regency face-to-face, with lecture and discussion methods using leaflet media. The participants of the activity were very enthusiastic, and based on the results of the evaluation, it was found that the participants became more knowledgeable about the importance of the Covid-19 vaccination.